(untitled) (Research, Society and Development, 2022)
Among the techniques that have attracted the attention of producers is the use of soil cover and the use of different spacings to complete a canopy. It is known that both techniques change the microclimate and can positively or negatively influence production. In this sense, the present work aimed to evaluate the influence of these factors in the development of a lettuce cv. Salad Bowl. The experiment was conducted at Três Irmãos Farm in the area destined for the cultivation of vegetables, located in the Rural Zone of Guaxupé-MG. The experimental design used was in randomized blocks, with four treatments and four replications, in a 2 x 2 factorial scheme (two spacings x 2 soil covers), totaling 16 plots. The plots were dimensioned in the form of a bed containing 1.0 x 1.5 m. The experimental factors consisted of two usual spacing of the cultivar (0.25 x 0.25 m; 0.30 x 0.30 m between rows and between plants, respectively) and two different soil coverings (bare soil, covering with dead straw ). The use of straw as vegetation cover decreased the thermal amplitude and the maximum values ​​of soil temperature, providing an increase in soil moisture up to 21 DAT and root volume in the two spacing between lettuce plants used. The 30 x 30 cm spacing provided an increase in fresh and dry biomass of the shoot, in the diameter of the head of lettuce and in the root volume in environments with and without vegetation cover.